Experimental determination of CO2 diffusion coefficient in aqueous solutions under pressure at room temperature via Raman spectroscopy: impact of salinity (NaCl). (25th June 2015) - Belgodere, Clément; Dubessy, Jean; Vautrin, Denis; Caumon, Marie‐Camille; Sterpenich, Jérôme; Pironon, Jacques; Robert, Pascal; Randi, Aurélien; Birat, Jean‐Pierre; Marshall, Craig P.
<x xml:space="preserve">Abstract</x> The accurate determination of the diffusion coefficient of dissolved CO2 in aqueous solutions is a key parameter to predict the transport of the dissolved gas in the aqueous solution of porous aquifers and caprocks in the context of the mitigation of greenhouse gases emissions. A better understanding of the diffusion kinetics of dissolved CO2 as a function of subsurface conditions is essential to ensure the integrity of CO2 storage in saline aquifers. Experimental data are available to predict the CO2 diffusion kinetics as a function of temperature and pressure. However, the impact of salinity on CO2 diffusivity is still poorly documented. In this work, the diffusion coefficients of dissolved CO2 were determined using in situ Raman microspectrometry in Fused Silica Capillaries in a range of salinity from 0.0 to 6.0 molNaCl kg−1H2O. The diffusion coefficient of CO2 dissolved in pure water at 21 ± 1 °C and 40 bar is 1.71 × 10−9 ± 0.06 m2 s−1. In the same conditions of pressure and temperature, the diffusion coefficient of dissolved CO2 decreases with salinity increase: from 0.0 to 6.0 molNaCl kg−1H2O (the diffusion kinetics of dissolved CO2 is divided by two). Consequently, the impact of salinity on the diffusion coefficient of dissolved CO2 must be taken into account to evaluate the transport of dissolved gases in the brine of the reservoir and caprock. Copyright © 2015 John Wiley & Sons, Ltd.